Compressive performance of all-grade engineered cementitious composites: Experiment and theoretical model. (30th May 2020) - Ding, Yao; Yu, Kequan; Mao, Weihao
Highlights: The compressive performance of all-grade ECC from 43 MPa to 115 MPa is comprehensively studied. A non-linear compressive model is proposed for all-grade ECC. A design compressive model of all-grade ECC is proposed and verified for practical application. Abstract: Compressive property of engineered cementitious composites (ECC) is essential when ECC is utilized as a structural material in the compression zone. More attention is deserved to clarify the compressive parameters and the constitutive model of ECC for a better practical application. In the present research, the compressive behavior of ECC with strengths ranging from 43 to 115 MPa was investigated and a constitutive model was developed. Uniaxial compressive tests were conducted on ECC under five water/binder ratios and the complete stress–strain curves were measured directly. According to the experimental results, the compressive parameters including strength, elastic modulus, toughness index, Poisson's ratio and average strain corresponding to the peak stress were calculated. The nonlinear compressive model was proposed according to the experimental stress–strain curves. In addition, a proper and simple stress–strain design model was established to describe the pre- and post-peak properties of ECC in uniaxial compression by using a quadratic function and a bilinear curve, respectively. The good agreement of the nonlinear model with the experimental results verified the credibility of the proposed model for the nonlinear analysis of ECC structural members under uniaxial compression. Additionally, the comparison between the stress–strain curves calculated by using the proposed design model and those obtained from previous researches of other kinds of strain-hardening cementitious composites demonstrates its wide applicability.